La Rupture Ou La Permanence De L’oral A L’ecrit - KALVA MWENE-MUBAMBI, Simon Pierre (International Journal of Scientific Research and Management (IJSRM), 2022)
Many semiological studies of literary genres focus their research on the written word to the detriment of the spoken word, which also contributes to the same goal: that of mirroring human society. However, in this article we propose to look for a bridge that connects oral literature to the so-called written one. Thus, speaking of the spoken word, we mean the traditional epic and of the written word the modern novel, but the two are not presented to us in the same way.